The Effect of the Self-schedule Strategy (K.W.L) on the Achievement and Retention of Information among Students of Al-Balqa Applied University in the Subject of Islamic Culture - Al-Thonibat, Mohammad (Dirasat: Educational Sciences, 2021)
This study aims at identifying the effect of the self-schedule strategy (K.W.L) on the achievement and retention of information among students of Al-Balqa Applied University on the subject of Islamic culture. The researcher used the semi-experimental method and then intentionally selected two divisions of the Islamic culture subject divisions taught by the same teacher to represent the sample of the study. Division No. (4) which holds (40) male and female students and Division No. (5) which holds (40) male and female students. After carrying out the equivalence of the two groups, division number (4) was chosen randomly to represent the experimental group that has been taught using the (K.W.L) strategy, Division No. (5) represented the control group that has been taught in an ordinary way. The researcher prepared an achievement test to measure achievement and retention of information. The results showed a statistically significant difference at the level of significance (ɑ≤0.5) between the mean scores of the control and experimental groups in the achievement and retention test in favor of the experimental group.